2020
DOI: 10.34172/apb.2021.078
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility Pattern of Caspofungin-Coated Gold Nanoparticles Against Clinically Important Candida Species

Abstract: Purpose: The present study was performed to examine whether caspofungin-coated gold nanoparticles (CAS-AuNPs) may offer the right platform for sensitivity induction in resistant isolates. Methods: For the purpose of the study, a total of 58 archived Candida species were enrolled in the research. The identification of Candida spp. was performed using polymerase chain reaction-restriction fragment length polymorphism and HWP1 gene amplification approaches. The conjugated CAS-AuNPs were synthesized and then chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Based on these properties, metal nanoparticles have broad applications in the drug delivery of antimicrobial agents [ 29 , 35 , 36 , 37 ]. The use of metal nanoparticles in combination with amphotericin B (AMB), caspofungin (CAS) and fluconazole (FCZ) may enhance its effectiveness against C. albicans [ 14 , 38 , 39 ]. Metal nanoparticles can play an important role in combating C. albicans strains resistant to antifungal drugs and biofilms formed on mucosa and medical devices [ 14 , 15 ].…”
Section: Metal Nanoparticlesmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on these properties, metal nanoparticles have broad applications in the drug delivery of antimicrobial agents [ 29 , 35 , 36 , 37 ]. The use of metal nanoparticles in combination with amphotericin B (AMB), caspofungin (CAS) and fluconazole (FCZ) may enhance its effectiveness against C. albicans [ 14 , 38 , 39 ]. Metal nanoparticles can play an important role in combating C. albicans strains resistant to antifungal drugs and biofilms formed on mucosa and medical devices [ 14 , 15 ].…”
Section: Metal Nanoparticlesmentioning
confidence: 99%
“…AuNPs have been typically investigated for the delivery of conventional antifungals. For example, Salehi et al [ 38 ] formulated the antifungal caspofungin by incorporating it into AuNPs (CAS-AuNPs). CAS, a member of the echinocandin class, inhibits the biosynthesis of the fungal cell wall component β-1,3-D-glucan [ 70 , 71 , 72 ].…”
Section: Metal Nanoparticlesmentioning
confidence: 99%
See 1 more Smart Citation
“…prepared caspofungin loaded gold nanoparticles. According to the author’s report, the nanoparticles that were prepared have demonstrated efficacy against resistant strains . Noorbakhsh et al conducted a study to investigate the effects of silver nanoparticles (Ag NPs) both alone and in combination with antifungal drugs, specifically fluconazole and griseofulvin, on T. rubrum .…”
Section: Advantages Of Nanocarriers Over Conventional Treatmentmentioning
confidence: 99%
“…According to the author’s report, the nanoparticles that were prepared have demonstrated efficacy against resistant strains. 134 Noorbakhsh et al conducted a study to investigate the effects of silver nanoparticles (Ag NPs) both alone and in combination with antifungal drugs, specifically fluconazole and griseofulvin, on T. rubrum . The findings indicated that the activity of T. rubrum was inhibited by Ag NPs alone when administered at a concentration of 10 μg/mL.…”
Section: Advantages Of Nanocarriers Over Conventional Treatmentmentioning
confidence: 99%